Supervisory Challenges of A Faculty Officer in Public Universities: The Case of the University for Development Studies - Seniwolib, Joseph Attiah (Innovare Journal of Education, 2025)
“The job of a Faculty Officer, which is primarily that of a supervisor, is a thankless one.” This paper reflects the writer’s displeasure and challenges as a Faculty Officer who is responsible for overseeing 302 staff members who work in both teaching and non-teaching capacities across thirteen departments. This paper is a review of the writer’s depressing reflection on the lack of job satisfaction he has experienced as a result of the numerous issues he had to deal with as a Faculty Officer. The issue of supervision in a system where workers in various departments appear to have dual loyalty—first and foremost to their heads of departments and secondly to the Faculty Officer, who represents the Registrar at the faculty level—is the most challenging and seemingly insurmountable duty. Since it is impossible for anybody to serve two masters at the same time, the article established the principle of unity of command as a necessity for efficient supervision. Most of the time, the people the Faculty Officer directly supervises may get conflicting or additional responsibilities from the Dean or Head of the Department. Accordingly, the article advises that under these circumstances, the Faculty Officer needs to establish open channels of communication with the Dean and Department Heads to decide the importance of tasks and the appropriate course of action. Additionally, the Faculty Officer must professionally design flexible work schedules and procedural modifications.